Teaching the Entrepreneurial Mindset Across the University An Integrative Approach - Bosman, Lisa; Fernhaber, Stephanie (Springer International Publishing : Imprint: Springer, 2021)
XXII, 135 p. 29 illus., 17 illus. in color.